2006
DOI: 10.1007/s00417-006-0356-9
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ T regulatory cells induced by LPS-activated bone marrow dendritic cells suppress experimental autoimmune uveoretinitis in vivo

Abstract: We suggest that DC maturation may be necessary for both tolerance and immunity, but differential levels of activation and/or cytokine production direct the outcome of DC-T cell interaction and this is determined by IL-12 production. T regulatory cells induced in vivo by contact with eDC are able to suppress disease in the EAU model by adoptive transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
4
20
0
Order By: Relevance
“…Additionally, the cells induced by CD40-B have greater suppressive capacity than those induced by imDCs. Similar to previous reports that cell-cell contact is required for the induction of CD4 1 Tregs by imDCs or plasmacytoid DCs, 27,28 we Figure 5 Generation of CD4 high CD25 1 Tregs is partially dependent on HLA-DR and CD80/86 expression. Naive CD4 1 CD25 2 T cells isolated from normal PBMCs were cocultured with allogeneic CD40-B (a) or imDCs (b) at a T/B or T/ DC ratio of 10/1 in the presence of neutralizing mAbs against HLA-DR, CD80/ CD86 or relevant isotype control for 9 days.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the cells induced by CD40-B have greater suppressive capacity than those induced by imDCs. Similar to previous reports that cell-cell contact is required for the induction of CD4 1 Tregs by imDCs or plasmacytoid DCs, 27,28 we Figure 5 Generation of CD4 high CD25 1 Tregs is partially dependent on HLA-DR and CD80/86 expression. Naive CD4 1 CD25 2 T cells isolated from normal PBMCs were cocultured with allogeneic CD40-B (a) or imDCs (b) at a T/B or T/ DC ratio of 10/1 in the presence of neutralizing mAbs against HLA-DR, CD80/ CD86 or relevant isotype control for 9 days.…”
Section: Discussionsupporting
confidence: 87%
“…We have previously demonstrated that LPS-activated BMDC secrete a different set of cytokines by varying the timing of LPS activation of freshly purified immature DC from B10RIII (H2 k ) mice (17,23). In this study, we confirm this result in C57BL/6 (H2 b ) mice: freshly purified BMDC are CD11C ϩlow CD11b ϩ CD4 Ϫ CD8a Ϫ expressing low levels of CD40, MHCII, and CD86 ( Fig.…”
Section: Differential Cytokine Secretion By Bone Marrow-derived DC (Bsupporting
confidence: 82%
“…Mature DC have in certain strains and protocols either induced or exacerbated autoimmune inflammation (2, 10 -16), whereas in other circumstances mature, immature, and semimature DC have inhibited disease (3,4,(17)(18)(19)(20)(21)(22). In addition, the cytokine profile of the DC (either IL-10 or IL-12 producing) seemed to affect the tolerizing effect of DC in certain models (23). In several models, administration of DC appears to lead to expansion of Tregs, whereas under other circumstances, they appear to suppress autoimmunity by shifting the Th1 cell profile toward the Th2 phenotype (18,24).…”
mentioning
confidence: 99%
“…Our previous data15, 42 showing that s.c. administration of LPS‐primed BMDC induces expansion of regulatory T cells at the skin‐draining lymph nodes, suggest that CD4 + regulatory T cells are likely to contribute toward the observed tolerogenic effect. Induction of regulatory T cells by LPS‐primed ET‐DC is probably a consequence of modified cell signalling induced in the DC by high‐dose LPS, which includes reduced signalling through NF‐ κ B (see also Fig.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously shown that LPS‐primed bone‐marrow‐derived DC (BMDC), inoculated subcutaneously (s.c.) as a single injection, suppressed experimental autoimmune uveoretinitis (EAU) in the C57BL/6 mouse, induced using interphotoreceptor retinoid‐binding protein (IRBP) peptide emulsified in complete Freund's adjuvant (CFA) containing Mycobacterium tuberculosis 15, 42. However, in our previous work the LPS extract contained small amounts of other TLR 15, 43, 44.…”
Section: Introductionmentioning
confidence: 94%